Ignatius Sancho and the British Abolitionist Movement, 1729-1786 - Barker-Benfield, G. J. author. aut Link
IX, 264 p. 6 illus., 2 illus. in color.
Keywords: “Ignatius Sancho, a man of rare accomplishments and talents, is an important figure in British black history, and in the story of Atlantic slave narratives. But he has, until now, lacked an appropriate biography. Barker- Benfield fills that gap with a biographical and literary study that is original, persuasive and grounded in wide-ranging and clever analysis and exposition. In the process, he has helped to secure Sancho at the centre of our understanding of British black history.” —James Walvin, Professor Emeritus in History, University of York “At last, Ignatius Sancho receives the thoughtful, sympathetic assessment the pioneer Anglo-African writer long has deserved. An acknowledged master of eighteenth-century cultural history, Barker-Benfield brings to his subject interpretive flair and characteristic insight. With original contributions to the history of antislavery and to the history of sexuality in late eighteenth-century England, this eloquent study willhold its value for many years to come.” —Christopher L. Brown, Professor, Columbia University in the City of New York This book highlights the significant role played by Ignatius Sancho (c. 1729-80), the first Black man to vote in England, in the British abolitionist movement. Examining the letters of Sancho, and especially his correspondence with the influential novelist and preacher, Laurence Sterne, the author analyses the relationship between sensibility and antislavery in eighteenth-century Britain. The book demonstrates how Sancho navigated the bawdy, riotous conditions of commercial London, which was the headquarters of a growing and war-torn Empire. It shows how Sancho mastered the fashionable and gendered language of the culture of sensibility, navigating the contemporary issues of race, slavery, and politics. The book addresses the White metropolitan and colonial preoccupation with Black men’s sexuality, which was intensified by the Somerset decision of 1772. Sancho’s was a unique and influential voice in eighteenth-century Britain, making this book an insightful read for scholars of anti-slavery as well as gender, race, and imperialism in British history. G. J. Barker-Benfield is Professor Emeritus of History at the State University of New York, Albany , New York, USA.